2017
DOI: 10.1002/mrm.26608
|View full text |Cite
|
Sign up to set email alerts
|

A time‐efficient acquisition protocol for multipurpose diffusion‐weighted microstructural imaging at 7 Tesla

Abstract: We estimated minimum acquisition requirements that enable diffusion tensor imaging, higher angular resolution diffusion-weighted imaging, neurite orientation dispersion, and density imaging and white matter tract integrity across whole brain with isotropic resolution of 1.8 mm in less than 11 min. Magn Reson Med 78:2170-2184, 2017. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Notably, our previous study found that mouse sublayer 4 neurons had a high degree of interconnectivity along the transverse hippocampal axis and the fiber tract identified in the TDI fiber analysis suggests a similar connectivity pathway exists in humans. As the resolution of MRI imaging technology continues to improve and microstructural imaging becomes clinically feasible and quantitatively-specific [30][31][32] , we believe the data here provides an important foundation for an integrative approach to bridge the gap between MRI imaging and human tissue histology.…”
Section: Discussionmentioning
confidence: 82%
“…Notably, our previous study found that mouse sublayer 4 neurons had a high degree of interconnectivity along the transverse hippocampal axis and the fiber tract identified in the TDI fiber analysis suggests a similar connectivity pathway exists in humans. As the resolution of MRI imaging technology continues to improve and microstructural imaging becomes clinically feasible and quantitatively-specific [30][31][32] , we believe the data here provides an important foundation for an integrative approach to bridge the gap between MRI imaging and human tissue histology.…”
Section: Discussionmentioning
confidence: 82%
“…These procedures are time consuming. For many clinical cases and studies, the scan time is limited because the patients are pediatric or elderly, have severe anxiety or other psychiatric conditions, or have difficulty holding their breath . Hence, longer SE or STE scans are not suitable, whereas ISTE is a viable way to increase the SNR in diffusion MRI in these conditions.…”
Section: Discussionmentioning
confidence: 96%
“…For many clinical cases and studies, the scan time is limited because the patients are pediatric or elderly, have severe anxiety or other psychiatric conditions, or have difficulty holding their breath. 15,29 Hence, longer SE or STE scans are not suitable, whereas ISTE is a viable way to increase the SNR in diffusion MRI in these conditions. Through improved SNRs, ISTE can facilitate clinical diagnosis and may potentially be applied to diffusion MRI radiomics to more accurately diagnose tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Multishell diffusion imaging, however, allows to decompose the diffusion signal into related tissue compartments [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] (see [46] , [47] for reviews), and therefore offers additional specificity to white matter composition. Here we utilized multishell diffusion images of ADNI-3 advanced neuroimaging data set to decipher the origin of the increased white matter MD associated with the cognitive decline.…”
Section: Introductionmentioning
confidence: 99%